Research on improving dynamic response ability of 30kW real fuel cell system based on operating parameter optimization. (8th January 2023) - Chen, Huicui; Liu, Yihao; Deng, Chenghao; Chen, Jinrui
Abstract: The dynamic response performance of fuel cell has a great significance on the output power and reliability of the system, which works mainly under load change conditions. This paper is aimed at the dynamic response of 30 kW fuel cell system. Combined with the mechanism analysis method and empirical method, a fuel cell system model including stack, air supply system, hydrogen supply system and thermal management system is established. The reliability of the model is verified from three aspects: polarization curve, load change condition and road spectrum. The method of improving the dynamic response capability of the system is qualitatively studied through simulation. The results show that the best dynamic performance and output performance can be obtained by increasing the inlet pressure to 2.5 bar, relative humidity to 80% and the stoichiometric ratio to 3, while the effect of the temperature is not significant. The coupling relationship between gas pressure and temperature, humidity and stoichiometric ratio is preliminarily studied, and the influence law is explained combined with the mechanism. It is found that increasing the stoichiometric ratio is conducive to increasing the oxygen pressure, while humidity and temperature have the opposite effect. This model can be further used to explore the coupling relationship of internal parameters of PEMFC under load change condition. Highlights: Detailed and thorough fuel cell system modeling process. Multilevel verification of model reliability. Influence law of multiple operating parameters in system dynamic response. The optimal working state is achieved by adjusting operating parameters. Study on coupling relationship between operating parameters in dynamic process.